Peran Shopee Affiliate Terhadap Peluang Kerja - Ira Yanti; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of shopee affiliate on job opportunities. This study uses internet searching and interview searching methods so that researchers as well as methods of library research approach can find broad results. The objects of this research are people who have joined the affiliate program to become affiliates and people who have felt the results of this shopee affiliate program. Shopee affiliate is an important program that will help create jobs. People who are able to take advantage of technological advances are the lucky ones. This is because he will not find it difficult to find jobs in the digital era like today. By utilizing the shopee affiliate program, you can pour your creative ideas and you can generate quite promising coffers. As we know, unemployment in Indonesia is quite high, this is because many people are not able to use technology, so they will miss a lot of information and lack of education that there are many jobs that we can get when we are able to use technology. This shopee affiliate program is a good program and quite promising for the general public. With the shopee affiliate program, this can be a job opportunity for the community and even students. Where this job is a job that is quite promising.